Prevalence of Eating Disorders in Individuals with Type 2 Diabetes: A Cohort Comparison of Patients and Controls - García-Mayor, Ricardo V.; García-Soidán, Francisco Javier; Salgado Barreira, Angel; on behalf of the TRACONAL STUDY GROUP (Experimental and Clinical Endocrinology & Diabetes Reports, 2017)
To determine the prevalence of eating disorders (ED) in a cohort of patients with type 2 diabetes (T2DM), to identify the more predominant forms of ED, and to clarify if ED is associated with impaired metabolic control. A cohort of 517 patients with T2DM aged≥40 years and a control cohort of 304 patients without diabetes, age and gender matched, were enrolled from 3 primary care centres. All subjects completed the Questionnaire of Eating and Weight Patterns-Revised (QEWP-R), followed by a structured interview (EDE 17th version). The overall prevalence of ED in patients with T2DM and control cohorts was 32.5% and 19.7%, respectively (p<0.001). The frequency of ED in the patients with T2DM cohort was significantly higher in male than in female: 61.9% vs. 38.1% of the ED, respectively (p<0.001). The most prevalent form was unspecified feeding or eating disorder, mainly uncontrolled picking at food in 24.6% of subjects, which is significantly more prevalent in the patients with T2DM cohort than in controls, 24.6% vs. 14.5% (p<0.001). Mean HbA1c was 7.15%±1.1% (55 mmol/mol, 159 mg/dL) and 6.84%±1.1% (51 mmol/mol,150 mg/dL) in patients with T2DM with ED and without ED, respectively (p=0.047). ED have a high prevalence in patients with T2DM, and the coexistence of type 2 diabetes and ED significantly affects metabolic control in these patients.
Keywords: diabetes; alimentation; obesity